Closed form solution of electromagnetic wave diffraction problem in a homogeneous bi‐isotropic medium. (16th January 2014) - Nawaz, Rab; Ayub, Muhammad
<x xml:space="preserve">Abstract</x> In this study, the problem of wave scattering of an electromagnetic field in a homogeneous bi‐isotropic medium by a perfectly conducting strip is theoretically analyzed. The crux of the study is a rigorous construction of a closed form solution in the complex domain. A series solution of electromagnetic plane wave diffraction problem in terms of the eigenfunctions that happen to be the generalized Gamma functions is found. In the transformed domain, the scattered field is physically interpreted by computing the convergence history, and thereby, higher order accurate solution has been obtained in complex domain in closed form. Copyright © 2014 John Wiley & Sons, Ltd.